THE IMPLEMENTATION OF 5S WORK CULTURE (SEIRI, SEITON, SEISO, SEIKETSU AND SHITSUKE) AT KHANSA OTO CARE - Tri Budiyanto Tri; Wisnu Nurcahyono (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Khansa Oto Care is a service provider to pamper vehicles with its services, namely car wash, nitrogen filling, oil and air filter change service, and accessories sale to make vehicles interiors comfortable. The work environment has not implemented the 5S system such as unused items are present in the work environment (Seiri), items have no storing place (Seiton), there is a lot of oil and plastic waste (Seiso), lack of caring for work equipment (Seiketsu), and the lack of the workers discipline in implementing the work culture (Shitsuke). The purposes of this research were to implement the 5S Work Culture and to find out its effect on the workers activities after the implementation The approach taken was by observation, distributing questionnaires using the Likert scale method, interviews, and documentation of the 5S implementation. Based on the implementation of the 5S Work Culture, it provided comfort and flexibility for the workers in carrying out their work (Seiri), it eased the workers to find the work items (Seiton), it provided comfort for the workers in doing their work (Seiso), it made the work equipment always in an optimal condition and reduced the risk of machine damage, thus, it could minimize the equipment damage cost (Seiketsu), and as an implementation form of commitment of the owner and the work (Shitsuke). Based on the program score, the score before the 5S implementation was 34.3% which was in the category of bad. After the implementation, it showed the score of 92.5% which was in the category of very good. It means that all of the workers recognized that the 5S Work Culture had a good impact on the work environment.